2015
DOI: 10.1039/c4mh00238e
|View full text |Cite
|
Sign up to set email alerts
|

Charge selective contacts, mobile ions and anomalous hysteresis in organic–inorganic perovskite solar cells

Abstract: High-efficiency perovskite solar cells typically employ an organic–inorganic metal halide perovskite material as light absorber and charge transporter, sandwiched between a p-type electron-blocking organic hole-transporting layer and an n-type hole-blocking electron collection titania compact layer. Some device configurations also include a thin mesoporous layer of TiO2 or Al2O3 which is infiltrated and capped with the perovskite absorber. Herein, we demonstrate that it is possible to fabricate planar and meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
344
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(372 citation statements)
references
References 44 publications
27
344
1
Order By: Relevance
“…Recently, transient p/n doping of intrinsic perovskite semiconductor as a result of ionic migration has been proposed by Snaith et al as a most probable model to explain slow photocurrent response and hysteresis. 69 However, there was no direct solid evidence that supports these proposed mechanisms and the origin of hysteresis remains in need of in-depth study. We have found that external bias voltage applied to the CH 3 NH 3 PbI 3 cell before obtaining the JV curve can lead to transient hysteresis that is significantly enhanced in planar-type cell structures.…”
Section: Mystery In Emergence Of Hysteresismentioning
confidence: 99%
“…Recently, transient p/n doping of intrinsic perovskite semiconductor as a result of ionic migration has been proposed by Snaith et al as a most probable model to explain slow photocurrent response and hysteresis. 69 However, there was no direct solid evidence that supports these proposed mechanisms and the origin of hysteresis remains in need of in-depth study. We have found that external bias voltage applied to the CH 3 NH 3 PbI 3 cell before obtaining the JV curve can lead to transient hysteresis that is significantly enhanced in planar-type cell structures.…”
Section: Mystery In Emergence Of Hysteresismentioning
confidence: 99%
“…As a result, the effective charge-transfer process through these interfaces can be changed by the distribution of ions, which are driven by the external electric field. [189] Li et al [115] also mentioned the often-observed kinks illustrated in Figure 6 in the J-V curve measurement. Several groups have observed a similar behavior, [15,117,128,190,191] and this phenomenon especially prevails when using fast scan rates.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 99%
“…Some "ETL-free" cells exhibited very low stabilized power output even though decent PCEs were obtained from J-V measurements. [ 55 ] Therefore, the working mechanism for these cells needs further investigation. We note that ITO and FTO behave as ETL, thus the term "ETL-free" should be taken with a grain of salt.…”
Section: Etl-free Cellsmentioning
confidence: 99%